COMPARISON OF THREE METHOD OF DNA EXTRACTION FOR METHICILLIN RESISTANT STAPHYLOCOCCUS AUREUS (MRSA) - Hanina Hanina; Humaryanto Humaryanto (Jambi Medical Journal : Jurnal Kedokteran dan Kesehatan, 2022)
Background: MRSA is a gram positive bacteria that has a peptidoglycan in the cell wall which is noteasy to lysis during the DNA extraction procces.Objectives: This study aimed to compare three DNA extraction method, using a conventional method, chelex method, and commercial kit in MRSA.Methods: This is a descriptive study with laboratory experiments. The sample was swabs of purulent wounds from inpatients in Jambi that were randomly selected. Swab sample identified as MRSA was extracted with three methods and tested using UV-Vis spectrophotometer.Results: The study results showed that the best DNA purity was found by DNA extraction usingcommercial kit (1.43), followed by chelex (1.14) and conventional (1.07) methods. Likewise, the highest concentration of DNA was DNA extraction using commercial kit (330 g/ml), followed by the chelex (78 g/ml) and conventional (54 g/ml) methods.Conclusion: A conventional method can be used as an extraction method that is easy to do and more economical. The best DNA purity and concentration was obtained in the kit extraction method, followed by chelex and conventional methods.Keywords: MRSA, extraction, conventional, chelex, kit